Effect of employing different grades of recycled polyamide 12 on the surface texture of laser sintered (LS) parts - Wan Yusoff, Wan Ahmad Yusmawiza; Pham, D. T.; Dotchev, K. (2009)
Laser sintering (LS) is one of the most versatile rapid prototyping (RP) processes currently available. One of the main advantages of employing this technology is that the non-sintered powder can be recycled and reused for further fabrication. Current powder recycling methodologies using a constant refresh rate with a very high portion of new material being added to the existing material reserve in order to maintain part quality and integrity. If the amount of the new powder is insufficient or if the recycled material is too “old” (i.e. has been recycled too many times), then the fabricated parts experience variation in their quality. Typical quality defects include; higher shrinkage rates and rougher than average surface textures often known as “orange peel”. This paper reports on an experimental study to investigate the significance of different deteriorated recycle Polyamide 12 (PA12) powders on the surface quality of products. The main aim of this research is to determine and acceptable ratio quantities of virgin to recycled powder that can be used before adversely affecting product surface texture. In this experiment, the melt flow rate (MFR) is chosen as a criterion to measure the recycled powder quality. The microstructures of external surface and cross sectional parts which employed the different grades of recycled powder quality were examined. The results of experiment suggested that the refresh powder target must be at least 27MFR in order to produce a LS good part surface.